2014
DOI: 10.5120/17150-7193
|View full text |Cite
|
Sign up to set email alerts
|

NER-FL: A Novel Named Entity Recognizer of Farsi Languageusing the Web-Based Natural Language Processors and Semantic Annotations

Abstract: Named Entity Recognition is a main task in the NLP area that has yielded multiple web-based natural language processors gaining popularity in the Semantic Web community for extracting knowledge from web data. These processors are generally located as pipelines, using dedicated APIs and various taxonomy for extracting, classifying and disambiguating named entities. In this paper, we address the problem of NER on Farsi language by proposing NER-FL, a novel semantic framework which unifies three popular named ent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Hence, it can be concluded that LD_Rank has high performance in LOD. As future works, we plan to explore positive outcomes of appropriate RDF ranking in different applications such as Question Answering [17] and NE disambiguation [18] in the context of property tagging.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, it can be concluded that LD_Rank has high performance in LOD. As future works, we plan to explore positive outcomes of appropriate RDF ranking in different applications such as Question Answering [17] and NE disambiguation [18] in the context of property tagging.…”
Section: Resultsmentioning
confidence: 99%